2011
DOI: 10.1039/c1cc14602e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tert-butyl peresters from aldehydes by Bu4NI-catalyzed metal-free oxidation and its combination with the Kharasch–Sosnovsky reaction

Abstract: A new tert-butyl peresters synthesis directly from aldehydes and TBHP was developed via Bu(4)NI-catalyzed aldehyde C-H oxidation. Mechanistic studies suggest that the protocol proceeds via a radical process. Combining the method with the Kharasch-Sosnovsky reaction offers a practical approach for the synthesis of allylic esters from simple aldehydes and alkenes via a two-step one-pot procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(85 citation statements)
references
References 72 publications
8
70
1
6
Order By: Relevance
“…Moreover, they are relatively consistent with the Cu/Fe atomic ratio selected for catalyst preparation and the formation of a copper-iron mixed oxide. 15 In our case, the treatment of 1,4-dioxane 1 and benzaldehyde 3 with TBAI in the presence of CuFeOx was negative, leading only to a mere 5% yield (Table 2, entry c). 7 However, when we employed t-butyl peroxybenzoate (TBPB) as the oxidant, the reaction proceeded quantitatively (Table 2, entry d).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Moreover, they are relatively consistent with the Cu/Fe atomic ratio selected for catalyst preparation and the formation of a copper-iron mixed oxide. 15 In our case, the treatment of 1,4-dioxane 1 and benzaldehyde 3 with TBAI in the presence of CuFeOx was negative, leading only to a mere 5% yield (Table 2, entry c). 7 However, when we employed t-butyl peroxybenzoate (TBPB) as the oxidant, the reaction proceeded quantitatively (Table 2, entry d).…”
Section: Resultsmentioning
confidence: 82%
“…The above-mentioned report by Wan et al describes a facile preparation of t-butyl peroxyesters from aldehydes catalyzed by TBAI. 15 This methodology was found to be very reproducible, robust, and suited for our purposes. Thus, we proceeded to the preparation of different peroxyesters that were reacted with 1,4-dioxane 1 in the presence of CuFeOx (Table 4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…166 Presumably, tert-butylperoxy esters are formed upon recombination of acyl and tert-butylperoxyl radicals (Scheme 45). The radical reaction mechanism is confirmed by the experiment in which the acyl radicals were trapped by TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl radical) (see Scheme 44).…”
Section: Scheme 44mentioning
confidence: 99%
“…It was noteworthy that a higher catalyst loading improved the yield to 66%, even after decreasing the reaction temperature (entry 19). It was reported that adding the phasetransfer catalyst 18-crown-6 into KI catalytic system could improve the yield significantly, [24] however, it had little influence on the current reaction (entry 20). Moreover, a higher reaction concentration could facilitate the annulation reaction (entry 21).…”
mentioning
confidence: 99%